2002
DOI: 10.1359/jbmr.2002.17.4.603
|View full text |Cite
|
Sign up to set email alerts
|

The Mode of Mechanical Integrin Stressing Controls Intracellular Signaling in Osteoblasts

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
67
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 40 publications
(42 reference statements)
4
67
0
1
Order By: Relevance
“…However, the evolution of the FAK phosphorylation state in adherent cells that are submitted to mechanical strain remains poorly investigated. Pommerenke et al showed that twisting magnetic beads coated with anti-␤1 antibodies and bound to osteoblastic cells leads to FAK activation (14). In the present study, immunostaining of phosphotyrosine residues essentially localized to focal adhesion plaques.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…However, the evolution of the FAK phosphorylation state in adherent cells that are submitted to mechanical strain remains poorly investigated. Pommerenke et al showed that twisting magnetic beads coated with anti-␤1 antibodies and bound to osteoblastic cells leads to FAK activation (14). In the present study, immunostaining of phosphotyrosine residues essentially localized to focal adhesion plaques.…”
Section: Discussionsupporting
confidence: 67%
“…Recent reports demonstrated that mechanical strain is able to activate ERK1/2 in several adherent cells such as mesangial cells (6), smooth muscle cells (7), and chondrocytes (8). In osteoblasts, ERK activation was mostly reported in fluid flow (9 -12), centrifugation (13), or magnetic drag force (14) experiments and in only one study using cyclic stretch (albeit combined with fluid flow) (15). However, cell stretch appears to be a relevant model of mechanical stimulus in the bone field (16,17) and provides specific osteoblastic responses (18).…”
mentioning
confidence: 99%
“…Osteoblasts as well as tumour cells express various integrins, and integrin signals are known to regulate osteoclast formation (Matsuura et al, 1996;Akatsu et al, 1998;Pommerenke et al, 2002). The molecules involved in cell-tocell recognition between MDA-231 cells and osteoblasts and the signal transduction for RANKL expression in osteoblasts are under investigation in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical interaction of integrins with the cytoskeleton involves accumulation of a number of cytoskeletally associated proteins [39,40]. Studies to directly apply mechanical forces to integrins on the apical surface of cells, provided insights into signaling mechanisms and biological responses of osteoblasts and mesenchymal stem cells [41][42][43][44]. These studies demonstrated a role of intracellular calcium in intracellular signaling which is required to activate and immobilize signaling proteins, like focal adhesion kinase to the actin cytoskeleton.…”
Section: Cells and Mechanotransductionmentioning
confidence: 99%